Nitrogen and sulfur co-doped chiral carbon quantum dots with independent photoluminescence and chirality. Issue 6 (10th April 2017) - Hu, Lulu; Sun, Yue; Zhou, Yunjie; Bai, Liang; Zhang, Yalin; Han, Mumei; Huang, Hui; Liu, Yang; Kang, Zhenhui
Abstract : Chiral CQDs exhibit strong PL and outstanding enantioselective electrochemical recognition ability. Moreover, chiral CQDs possess independent PL and chiral properties. Abstract : Chiral nanostructures have attracted extensive interest as components for chiral applications. Carbon quantum dots (CQDs) with superior properties, including low toxicity and good biocompatibility, can render the field of QDs with more potential biological applications in bioimaging, biosensors, and drug delivery. Herein, we report the fabrication of nitrogen and sulfur co-doped chiral CQDs (l -/d -CQDs) with strong symmetrical circular dichroism (CD) signals at about 212 and 240 nm. These chiral CQDs exhibit strong photoluminescence (PL) emission (at 460 nm) and outstanding enantioselective electrochemical recognition ability. A series of experiments further confirms that these chiral CQDs possess independent PL and chiral properties. With a temperature increase, PL is quenched with a good linear correlation of 0.992, whereas the CD signals remain almost the same. On the other hand, the PL ofl - ord -CQDs shows no difference towards small chiral molecules detection with right or opposite configuration. In addition, thel - ord -CQDs excited with circularly polarized light (CPL) show similar PL properties regardless of their right or left configuration.